The effect of immunomodulatory treatment on multiple sclerosis fatigue. Issue 7 (16th June 2004) - Metz, L M; Patten, S B; Archibald, C J; Bakker, J I; Harris, C J; Patry, D G; Bell, R B; Yeung, M; Murphy, W F; Stoian, C A; Billesberger, K; Tillotson, L; et al.
Abstract : Objective: To assess the effects of glatiramer acetate and β interferon on fatigue in multiple sclerosis. Methods: Fatigue was measured at baseline and six months using the fatigue impact scale (FIS). Groups (glatiramer acetate and β interferon) were evaluated for the proportion improved, using Fisher's exact test. Logistic regression analysis assessed the relation between treatment group and improvement and controlled for confounding variables. Results: Six month paired FIS assessments were available for 218 patients (76% female). Ages ranged between 19 and 61 years, with 86% having relapsing-remitting disease. Glatiramer acetate was used by 61% and β interferon by 39%. At baseline, total FIS and subscale scores were comparable in the two groups. More patients improved on glatiramer acetate than on β interferon on total FIS (24.8% v 12.9%, p = 0.033; adjusted odds ratio = 2.36, 95% confidence interval 1.03 to 5.42), and on physical (28.6% v 14.1%, p = 0.013) and cognitive subscales (21.1% v 10.6%, p = 0.045). Logistic regression analysis confirmed the association between glatiramer acetate use and improved fatigue, after accounting for baseline group differences. Conclusions: The odds of reduced multiple sclerosis fatigue were around twice as great with glatiramer acetate treatment as with β interferon. Confirmation of this result is required.